Методи оцінки безпеки транспортних потоків - Деменчук, Владислав; Янішевський, Сергій (Видавництво Львівської політехніки, 2015)
This report deals with analysis of the main methods for evaluation the road safety. On the basis of implemented analysis it is offered the method for evaluation the safety of traffic flow , which is grounded on the analysis of characteristics of time intervals distribution in the transport (traffic) flow.
Methods for evaluation the traffic flow